2018
DOI: 10.3390/socsci7100194
|View full text |Cite
|
Sign up to set email alerts
|

Housing Discrimination and Health: Understanding Potential Linking Pathways Using a Mixed-Methods Approach

Abstract: Few studies have examined the impact of housing discrimination on health. This study explores potential pathways linking housing discrimination and health using concept mapping, a mixed-method approach. Participants included employees from twenty Fair Housing Organizations nationwide who participated in two online sessions, brainstorming, and structuring. Responses were generated representing biological, social, economic, and physical connections between housing discrimination and health. Using hierarchical cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…40 Additionally, the practice of redlining might influence the placement of healthcare services, thus potentially limiting future access to care and hence, might contribute to existing asthma disparities. 16,41 Furthermore, the historical context upon which institutions in these communities function can perpetuate inequity. For example, two studies published in the past few years found that historical concentrations of enslaved populations during the 1800s in the southern USA are associated with present-day poor health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…40 Additionally, the practice of redlining might influence the placement of healthcare services, thus potentially limiting future access to care and hence, might contribute to existing asthma disparities. 16,41 Furthermore, the historical context upon which institutions in these communities function can perpetuate inequity. For example, two studies published in the past few years found that historical concentrations of enslaved populations during the 1800s in the southern USA are associated with present-day poor health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic racism refers to the embedded power in institutions and other structures led by those with both known and unrecognized biases that are reflected in regulations, policies and practices, perpetuating inequitable access to resources and opportunities [13]. Amongst Black communities, longstanding marginalization has led to higher rates of housing instability, financial insecurity, and essential service inaccessibility compared to White communities [14][15][16]. For instance, Black families in Michigan report 2.5 times higher rates of poverty [17] and 43% lower household incomes [18] than White families.…”
Section: Introductionmentioning
confidence: 99%
“…Longstanding marginalization of Black communities has led to higher rates of housing instability, financial insecurity, and essential service inaccessibility compared to White communities. [9][10][11] For instance, Black families in Michigan report 2.5 times higher rates of poverty 12 and 43% lower household incomes 13 than White families. Flint and Detroit, the residents of which are predominantly Black, are the the second and fourth poorest cities in the US, respectively.…”
Section: Introductionmentioning
confidence: 99%